EVALUATION OF BANANA GENOTYPES FOR GROWTH AND YIELD UNDER NORTHERN DRY ZONE OF KARNATAKA - B. S. SAGAR,; B. RAJU,; KULAPATI HIPPARAGI,; S. N. PATIL,; B. R. SAHITHYA, (The Bioscan, 2014)
Banana is one of the most important food and cash crops in Karnataka. However, most of the cultivars grown particularly the local ones are low yielders and are thus not very suitable for commercial production. To find the suitable genotype twenty three genotypes were evaluated. Among them, the maximum plant height (305.00 cm) was recorded in the genotype Monthon which found the tallest at 240th day after planting and the minimum plant height (147.81cm) was recorded in the genotype Kayipallebale. The genotype YangaviKM-5 exhibited the maximum plant girth (76.27 cm) however, it was found minimum (46.45cm) in the genotype Pisanglilin. The highest leaf length (166.67 cm) and leaf area (0.82 m2 ) were observed in Robusta genotype. Whereas, the lowest leaf length (123.63cm) and leaf area (0.45m2 ) were recorded in the genotype Mitli. The genotype Hanuman recorded the maximum number of leaves (17.33) and finally the highest yield (43.07 t ha-1) and the minimum number of leaves (10.67) was recorded in the genotypes Elakkibale and Pisanglilin. Among the genotypes evaluated, the genotype Mitli performed very poor with the lowest yield (3.84 t ha-1). From the present investigation, it could be concluded that the genotype Hanuman is suitable to maximize the yield under Northern Dry Zone of Karnataka.